The Effectiveness of the Strategy of the Indonesian Armed Forces’ Habema Operation Command in Preserving Peace in Papua - Faiq Dhiya Ulhaq Mauludi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2026)
This analysis explores the territorial operation strategies employed by the Habema Operational Command Task Force of the Indonesian National Armed Forces (TNI) in counterinsurgency efforts against threats posed by the Free Papua Movement (OPM). The discussion focuses on identifying strategic actions taken, evaluating their effectiveness, and assessing their contributions to security stability and community welfare in Papua. A qualitative research method was applied, relying on a document analysis as primary data sources. The findings reveal that territorial approaches emphasizing community participation and welfare-based development programs are effective in mitigating conflict potential. These insights contribute to the body of knowledge on modern counterinsurgency, particularly in regions with complex geographical and sociocultural challenges.